Analisis hedging determinants dengan instrumen foreign currency derivative - Kodriyah Kodriyah; Nikke Yusnita Mahardini; Rosnia Rosnia (Penerbit Goodwood, 2019)
Purpose: The purpose of this study is to analyze the factors that influence hedging through foreign currency derivative instruments Research methodology: The method used was causal quantitative research. The research population was Manufacturing Companies in the Automotive Sub Sector Listed on the Indonesia Stock Exchange with the research period from 2014 to 2018 amounted to 60 companies, and a sample of 35 companies was obtained from purposive sampling technique. The Data analysis techniques used were logistic regression analysis and processed using SPSS Statistics 25 Results: The study proves that firm size has a significant effect on hedging decisions through derivative instruments, Growth opportunity have a significant effect on hedging decisions through derivative instruments, leverage has a significant effect on hedging decisions through derivative instruments, whereas liquidity does not affect hedging decisions through derivative instruments. Limitations: This research was focused on managing the risk of fluctuations in foreign currency rates by hedging through foreign currency derivative instruments and the factors that influence their use, i.e., firm size, Growth opportunity, leverage and liquidity. The research was also limited to companies manufacturing automotive and sub-sector components listed on the Indonesia Stock Exchange (IDX) in 2014-2018. Contribution: Investors can provide guidance in assessing and intervening the company's performance. For prospective investors, this research can be a reference in planning investment in a particular company that can be responsive in protecting the company. And for companies that conduct transactions with foreign currencies, companies should consider hedging to protect their companies from the risk of changes in currency values. Keywords: Hedging, Firm Size, Growth opportunity, Leverage and Liquidity